Integrated voice and RS232C data capability for a personal computer / [mikrofilem] - 194281 Neoh, Kim Koon; Yong, Chea Hwa (Skudai : Universiti Teknologi Malaysia, 1991)
Project Paper (Bachelor of Electrical Engineering) -- Universiti Teknologi Malaysia, 1991